Carp farming - Michaels, V.K. (Fishing News Books, 1988)
Centuries ago the carp became the most common table fish in Europe. Quality has been improved by selective breeding and its farming is more economical than most of the salmonids. Wild fish are popular with anglers, while the koi carp are much prized ornamental fish.